A new [4 + 1]/[4 + 2]bicycliaztion strategy for accessing functionalized indeno[1, 2-b]pyran-2-ones. Issue 78 (5th August 2016) - Jiang, Bo; Fu, Rong; Qiu, Jiang-Kai; Yu, Yan; Wang, Shu-Liang; Tu, Shu-Jiang
Abstract : A new base-promoted bicyclization strategy for the synthesis of functionalized indeno[1, 2- b ]pyran-2-ones has been established from readily accessible o -phthalaldehydes (OPA) and the preformed 1-arylethylidenemalononitriles. Abstract : A new base-promoted bicyclization strategy for the synthesis of functionalized indeno[1, 2- b ]pyran-2-ones has been established from readily accessible o -phthalaldehydes (OPA) and the preformed 1-arylethylidenemalononitriles. The reaction pathway involves an aldol addition, 5- exo-trig carbocyclization and 6- exo-dig oxo-cyclization sequence, resulting in continuous multiple C–C and C–O bond formation.